THE IMPLEMENTATION POLICY OF THE NATIONAL COMMUNITY EMPOWERMENT PROGRAM (PNPM) AT MASALLE DISTRICT OFFICE ENREKANG REGENCY - Ohoiwutun, Yosephina (Journal of Humanity, 2015)
This research aims to find out how the implementation of the National Program for community empowerment policy-development of socio-economic Infrastructure of the territory (PNPM-PISEW) in Sub district Office Problem and how it impacts the national community empowerment Program-social economic infrastructure development Areas (PNPM-PISEW) towards the implementation of the national program Office policy Sub Masalle. The population in this research is the number of whole populations examined, which include government officials, community leaders and the community around the site or who benefit from the existence of the PNPM-PISEW. While the sample was about 10 (ten) people of the total population using Random Sampling. From the results of research and analysis conducted, it can be drawn the conclusion that the influence of National Community Empowerment Program policies-social economic infrastructure development Areas (PNPM-PISEW), and socio-economic impact of national community empowerment Program-social economic infrastructure development Areas (PNPM-PISEW) in Sub district Office Masalle. Very positive and significant with a score of 4.27. Category Either.